Reflexões sobre o efeito retroativo do celpe-bras no curso de português língua estrangeira/segunda língua em contexto institucional - Conceição, Karina Corrêa (2021)
Studies developed in the area of learning assessment have revealed that exams of high social relevance are instruments that have potential impacts on all educational processes - considering the practices, attitudes and perceptions of teachers and students, the teaching materials used and the educational institutions – promoting what the literature in evaluation calls washback or backwash, in Portuguese, “retroactive effect” (ALDERSON; WALL, 1993; SCARAMUCCI, 1998b, 1999c, 2000, 2004; GUIMENEZ, 1999). This qualitative and ethnographic-based research aimed to investigate the retroactive effect of the exam to obtain the Certificate of Proficiency in Portuguese Language for Foreigners (Celpe-Bras) in the teaching of Portuguese as a Foreign Language/Second Language (PLE/ L2), of the Language Center (Núcleo de Línguas), of the Federal University of Espírito Santo (UFES), from its accreditation as a post applying the exam, in 2016. For this, we proceeded with the survey and triangulation of the data generated in semi-structured interviews and in the documental analysis (of tests applied in the PLE/L2 course, in the period 2014-2015 and 2017-2018 and activities of the 2019 course), observing how the PLE/L2 course was before and after 2016. The descriptions and analysis of the data revealed the existence of a retroactive effect in the teaching of PLE/L2, evidencing changes in the perceptions and attitudes of former teachers and former advisor of the course, in the textual proposals of performance assessments applied at the end of the course, the course modules, in addition to having effects on the teaching materials and the use of the textbook collection adopted in the course. We hope that this work will contribute to the panorama of research carried out on the retroactive effect in the Brazilian context, in addition to fostering more studies on the phenomenon and on PLE/L2 in the state of Espírito Santo and in other institutional contexts.